Cellular immune states in SARS-CoV-2-induced disease - Mortezaee, Keywan; Majidpoor, Jamal (Frontiers in Immunology, 2022)
General immune state plays important roles against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Cells of immune system are encountering rapid changes during the acute phase of SARS-CoV-2 induced disease. Reduced fraction of functional CD8+ T cells, disrupted cross-talking between CD8+ T cells with dendritic cells (DCs) and impaired immunological T cell memory, along with the higher presence of hyperactive neutrophils, high expansion of myeloid-derived suppressor cells (MDSCs) and non-classical monocytes, and attenuated cytotoxic capacity of natural killer (NK) cells are all indicative of low efficient immunity against viral surge within the body. Immune state and responses from pro- or anti-inflammatory cells of the immune system to SARS-CoV-2 are discussed in this review. We also suggest some strategies to enhance the power of immune system against SARS-CoV-2 induced disease.